ANALISIS PEMENUHAN HAK NARAPIDANA HAMIL DAN MENYUSUI DI RUMAH TAHANAN (RUTAN) PEREMPUAN KELAS IIA MEDAN - DEWANTARA SIREGAR, AGUNG ADIPA (Politeknik Pengayoman Indonesia, 2024)
This study aims to analyze the fulfillment of the rights of female convicts who are pregnant and breastfeeding at the Class IIA Women's Detention Center in Medan. This study uses empirical legal research methods by collecting data through structured interviews with pregnant and lactating women inmates as well as analysis of documents related to regulations and policies. The results of the study show that even though there are adequate lactation room facilities, there are still challenges in fulfilling the rights of female prisoners such as privacy, health and fair treatment. The implications of this research are the need to increase awareness, improve facilities, more inclusive policies, and pay attention to the welfare of mothers and fetuses.